2016
DOI: 10.1016/j.ejca.2016.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Serum glucose and hemoglobin A1C levels at cancer diagnosis and disease outcome

Abstract: Background Despite the lack of scientific data, many cancer patients hold the belief that glucose “feeds” cancer and might affect disease outcome. We aimed to evaluate associations between glucose, hemoglobin A1C (HbA1C), and survival among individuals with diabetes and diabetes associated cancers. Methods Five retrospective cohort studies were conducted in a large population-representative database. The study population included all patients with diabetes and an incident diagnosis of colorectal, breast, bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 41 publications
3
14
1
Order By: Relevance
“…These results are in agreement and extend previous reports in cancer patients with T2D, in whom HbA 1c levels were evaluated as a marker of glycemic control[41,42]. In particular, Siddiqui et al[41] reported that poorly controlled T2D - defined as a HbA 1c level ≥ 7.5% - was independently associated with a more advanced CRC stage at time of diagnosis and poorer 5-year survival, thus suggesting that in CRC patients with T2D, poor glycemic control is associated with a clinically aggressive cancer phenotype.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are in agreement and extend previous reports in cancer patients with T2D, in whom HbA 1c levels were evaluated as a marker of glycemic control[41,42]. In particular, Siddiqui et al[41] reported that poorly controlled T2D - defined as a HbA 1c level ≥ 7.5% - was independently associated with a more advanced CRC stage at time of diagnosis and poorer 5-year survival, thus suggesting that in CRC patients with T2D, poor glycemic control is associated with a clinically aggressive cancer phenotype.…”
Section: Discussionsupporting
confidence: 93%
“…However, the small number of T2D patients enrolled did not confer enough power to perform a separate subgroup analysis. On the other hand, Boursi et al[42] reported no association between HbA 1c levels within 6 mo prior to cancer diagnosis and overall survival for CRC. This study is barely comparable with the results obtained in ours, since it enrolled only T2D patients in whom HbA 1c was evaluated as a marker of glycemic control.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have explored the relationship between glycemic control and outcomes in cancer patients with or without diabetes. The four studies found used different methods and designs: two were retrospective,[ 20 21 ] one was cross-sectional,[ 22 ] and one was longitudinal. [ 14 ] In addition, there was little consistency in how glycemic control was measured across studies.…”
Section: Glycemic Control During Treatmentmentioning
confidence: 99%
“…Two studies found no association between with glycemic control level and outcomes in cancer patients. [ 20 22 ] Boursi et al . used previously obtained HbA1c levels, but patients’ glycemic control level at the time of their cancer diagnosis and while they were undergoing treatment were unknown.…”
Section: Glycemic Control During Treatmentmentioning
confidence: 99%
“…To our knowledge, the 4 studies that have investigated diabetes management patterns found that glucose control, medication adherence, and self-management behaviors declined after a cancer diagnosis. [11][12][13][14] However, these studies were limited to individuals undergoing chemotherapy, [12][13][14][15] measured glucose at the time of cancer diagnosis but not after the initiation of cancer treatment, 13 and had very small sample sizes. 14,15 The objective of the current study was to describe patterns of diabetes management among patients with cancer in the year before and after diagnosis.…”
Section: Introductionmentioning
confidence: 99%